Grado y factores de riesgo de pterigión en los habitantes de la parroquia Ciano del cantón Puyango - Jaramillo Jaramillo, Karla Mercedes (2022)
Pterygium is an ocular pathology consisting of the abnormal growth of the conjunctiva on the cornea, being a degenerative phenomenon caused by factors associated with exposure to sunlight, environmental dryness, dust, among other elements, contracting consequences such as limited vision and stigmatism.. As a general objective, to determine the prevalence of pterygium according to sex, age group and predominant degree; determine the risk factors and the relationship between the degrees with the risk factors. It was quantitative, descriptive, cross-sectional and retrospective, for which inductive, deductive, analytical and statistical methods were used, under a questionnaire adapted by the author in order to establish the levels of pterygium and risk factors. It was applied to 101 residents diagnosed with pterygium in the Ciano parish. From the main results we have that there is a prevalence of the female sex with greater severity of pterygium, in the age ranges from 40 to 64 years, with a higher presence in grade I, being the main risk factors, with the highest percentages in light solar, dust, heat and wind. For the last objective, the correlation of chi square with CI 95 indicated significant statistical values for the degrees: IV related to occupation and sun exposure; III on direct exposure to smoke; I and II biological factors such as dry eyes and family history, and I to the factors of chemical and environmental agents. Given this analysis, it is concluded that the greater the exposure of the risk factors, the greater the predisposition to suffer from pterygium.